Frequency of Thrombocytopenia in Malaria Patient at Tertiary Care Hospital - Muhammad Khalid, Komal Iqbal, Muhammad Nadeem, Khalid Khan, Aqeela Kousar, Sidra Rao, Muhammad Abrar, Fiza Abbas (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Hematological disorders, including anemia, thrombocytopenia and leukopenia are quite frequent among malaria patients. Objective: To assess the frequency of thrombocytopenia in malaria patient at tertiary care hospital Methodology: This study was descriptive, cross-sectional study carried out at the medicine department, Qazi Hussain Ahmad Medical Complex, Nowshera for a period of six months from May 2022 to October 2022. Pre-designed proforma was used to collect patient information, such as demographics and medical history. A hematology analyzer was used to calculate the hematological variables from the CBC results. All the collected data was analyzed by using IBM SPSS version 23. Results: There were 83 (55.33%) males and 67 (44.77%) females. The overall frequency of thrombocytopenia amongst 150 patients with malaria was 90% (n=135). Amongst patients with thrombocytopenia, grade 1 thrombocytopenia was observed in 75 (50%) patients, grade 2 in 38 (25.33%) patients, grade 3 in 23 (15.33%) patients while grade 4 thrombocytopenia was observed in 14 (9.33%) patients. Conclusion: Our study concludes that thrombocytopenia is highly prevalent amongst patients with malaria. This leads us to the conclusion that the platelet count is a useful first-stage screening parameter in individuals with acute febrile illness. Keywords: Thrombocytopenia; Malaria; p.vivax; p.falsiparum